Judah in the Shadow of Babylon - Beaulieu, Paul-Alain (Hebrew bible and ancient Israel, 2020)
This article surveys the penetration of the Neo-Babylonian empire in the southern Levant and the gradual disestablishment of the kingdom of Judah by Nebuchadnezzar II. Particular attention is paid to the strategic interests of Babylon in the region, the way conquered territories were viewed from the imperial perspective, and the impact of these factors on the destruction of Judah, its capital Jerusalem, and the exile of a large portion of its inhabitants to Babylonia.